A STEM Narrative: 15 Years in the Making - Blackley, Susan; Howell, Jennifer (Edith Cowan University, 2015)
Since its inception in the late 1990s, STEM has continued to attract attention and sizeable funding in the US, UK, and Australia. This paper narrates the development of the STEM movement both nationally and internationally, and analyses both the influences that have progressed its evolution and those that have stymied authentic STEM practices. The pervading rhetoric of ‘STEM crisis’ is considered through a global lens, and is resolved as a geo-political phenomenon. The strident voice of the US in the STEM narrative is tempered by investigating the approach to STEM in European, Asian, and developing countries. Two perspectives are described in the narrative: the political and the educational. Each perspective has an apparently differing agenda that has resulted in little success in achieving the desired and much-publicised STEM outcomes. The paper concludes with suggestions of two courses of action that would most likely achieve the outcomes.